Devil tales - Boyle, Virginia Frazer, 1863-1938; Frost, A. B. (Arthur Burdett), 1851-1928 (Salt Lake City, UT : Project Gutenberg, 2023)
"Devil Tales" by Virginia Frazer Boyle is a collection of short stories written in the early 20th century. The work delves into folklore and supernatural themes, centering on the lives of African American characters and their interactions with mystical elements and the devil. Through rich storytelling infused with cultural references, it explores themes of love, jealousy, and the struggle for freedom. The opening of "Devil Tales" sets the stage with the introduction of a character named Solon, who is experiencing marital troubles with his wife Juno. Their quarrel, intensified by Juno's suspicions regarding Solon$1 (Bs late-night absences, leads her to consult a local hoodoo practitioner for guidance. The narrative highlights the use of folk beliefs and magic as Juno embarks on a quest to uncover the truth about Solon$1 (Bs activities, hinting at a deeper exploration of themes surrounding deception, superstition, and the moral complexities within their community. (This is an automatically generated summary.)s
Old Cinder Cat -- "A kingdom for Micajah" -- The devil's little fly -- Asmodeus in the quarters -- The taming of Jezrul -- Dark er de moon -- The other Maumer -- Stolen fire -- The black cat -- 'Liza.
Release date is 2023-04-01
Charlene Taylor, Les Galloway and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Short stories, American; African Americans -- Fiction; Devil -- Fiction